Pemanfaatan Lahan Pekarangan untuk Mendukung Lingkungan Sehat, Ketercukupan Gizi, dan Kemandirian Pangan Lokal di Desa Moutong, Kabupaten Bone Bolango - Machmud, Rizan; Monoarfa, Valentina; Wowor, Moh. Afriansyah (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2025)
The Thematic Community Service Program (KKN) in Moutong Village, Tilongkabila District, Bone Bolango Regency, focused on utilizing home gardens to promote a healthy environment and improve community nutrition. The activity aimed to enhance local food self-sufficiency through counseling, training on fast-harvest crop cultivation, organic compost production, and family nutrition education. The implementation involved field observations, hands-on practice, group discussions, and evaluation through pre-test and post-test. Through pre- and post-tests.The program was carried out from August to November 2025. The results showed an increase in community knowledge and skills in managing home gardens, marked by the establishment of model mini gardens and a “Healthy Yard Community.” In addition to improving household food availability, the activity also contributed to stunting prevention through parenting and balanced nutrition education. The success of this program was supported by the active participation of the community, village government, and KKN students. Thus, home garden utilization has proven to be an effective strategy for empowering communities toward healthy, independent, and sustainable food systems.